A new species of Leptodactylus Fitzinger (Anura, Leptodactylidae, Leptodactylinae) from montane rock fields of the Chapada Diamantina, northeastern Brazil - Carvalho, Thiago Ribeiro De; Leite, Felife Sá Fortes; Pezzuti, Tiago Leite (Zootaxa, 2013)
In this paper, we describe a new species of the Leptodactylus fuscus group on the basis of adult morphology and advertisement call, occurring restricted to montane rock fields of the Chapada Diamantina, northern portion of the Espinhaço Range, central State of Bahia, northeastern Brazil. In addition, we re-describe the advertisement call of L. camaquara from its type locality. Leptodactylus oreomantis sp. nov. represents the first species of the genus occurring restricted to montane rock fields of the Chapada Diamantina, northeastern Brazil, whereas the other three species of the L. fuscus group assumed to be restricted to montane field environments (L. camaquara, L. cunicularius, and L. tapiti) occur in association with mountain ranges of southeastern or central Brazil.